Nanoparticles of highly soluble polypyrrole and silver as an antimicrobial alternative in vitro and in silico against Staphylococcus warneri - Nayara Andreo; Betilde de Matos Silva; Danillo Sales Rosa; Priscila Izidro de Figueirêdo; Chirles Araújo de França; Fernando Antonio Gomes da Silva Júnior; Helinando Pequeno de Oliveira; Leonardo Broetto; Mateus Matiuzzi da Costa (The Microbe, 2025)
Staphylococcus warneri has not been extensively studied in the context of mastitis pathophysiology. In addition to its multidrug resistance, its persistence and the search for antimicrobial alternatives deserve attention. In this context, polypyrrole and silver nanoparticles stand out due to their antimicrobial properties. This study aimed to test highly soluble polypyrrole (Hs-PPy) and silver (SNPs) nanoparticles as antimicrobial and antibiofilm agents, as well as the molecular binding of Hs-PPy to resistance and persistence proteins of S. warneri. Eight persistent S. warneri isolates from goat mastitis resistant to enrofloxacin (ENO) and one reference strain, were used. The antimicrobial activity of Hs-PPy and SNPs was determined through broth microdilution. The synergistic potential of Hs-PPy was evaluated in combination with SNPs and ENO using the checkerboard method. Biofilm production and interference were assessed using the microplate adhesion test. Bacterial viability in response to Hs-PPy was analyzed using the BacLight™ Kit. In silico interactions between Hs-PPy and antimicrobials were investigated against 16 S. warneri proteins related to resistance and persistence. Hs-PPy shown inhibitory and bactericidal activity at 62.5 μg/mL. SNPs did not exhibit antimicrobial or antibiofilm activity at tested concentrations. Additive interactions were observed between Hs-PPy and SNPs, and synergistic interactions with ENO. A significant reduction in biofilm production was observed in three isolates using ½ MIC of Hs-PPy. The bacterial viability assay confirmed the antimicrobial potential of Hs-PPy. Compared to tested antimicrobials, Hs-PPy shown lower binding energies with almost all resistance proteins and with all persistence proteins. It is concluded that in vitro, Hs-PPy has bactericidal and antibiofilm potential against S. warneri. Moreover, the compound was capable of reducing the effective concentrations of SNPs and ENO, making it a promising alternative for combating resistance. Additionally, in silico analysis revealed that Hs-PPy acts on several proteins involved in S. warneri resistance and persistence.